The level of motivation and barrier to physical education learning: the perspective of boarding school students - Kurniawan, Rama; Khamid, Wiji Bagus Sasmito; Putra, Surya Adi (Journal of Science and Education (JSE), 2023)
Motivation in physical education learning is essential for achieving educational goals. In achieving this, there is also a barrier that can hinder achieving an educational goal. There have been many studies about this in public schools. However, boarding schools still need to be done considering the different characteristics of students between public school students and boarding schools. The purpose of this study was to determine the description of the motivation and barriers of high school students in physical education learning from the perspective of boarding school students at Modern High School Al-Rifa'ie Gondanglegi. The technique used is a survey with quantitative descriptive methods. The number of samples is 215 students divided into classes X, XI, and XII, the distribution of samples using simple random sampling. The test instrument used a questionnaire. The results of data analysis of student motivation and barriers show the level of student motivation with the highest percentage of intrinsic motivation at 25% and the lowest percentage of motivation at 14%. As for student barriers, the highest percentage result is external barriers at 56%, and the lowest percentage is internal barriers at 44%. In conclusion, of the five motivation categories that have been researched, intrinsic motivation obtained the most dominant results compared to other motivation categories. As for student barriers, it can be concluded that of the two factors that have been studied, external barriers obtain more dominant results than internal barriers.